Comparing neural correlates of visual target detection in serial visual presentations having different temporal correlations - Luo, An; Sajda, Paul (Frontiers in Human Neuroscience, 2009)
Most visual stimuli we experience on a day-to-day basis are continuous sequences, with spatial structure highly correlated in time. During rapid serial visual presentation (RSVP), this correlation is absent. Here we study how subjects' target detection responses, both behavioral and electrophysiological, differ between continuous serial visual sequences (CSVP), flashed serial visual presentation (FSVP) and RSVP. Behavioral results show longer reaction times for CSVP compared to the FSVP and RSVP conditions, as well as a difference in miss rate between RSVP and the other two conditions. Using mutual information, we measure electrophysiological differences in the electroencephalography (EEG) for these three conditions. We find two peaks in the mutual information between EEG and stimulus class (target vs. distractor), with the second peak occurring 30–40 ms earlier for the FSVP and RSVP conditions. In addition, we find differences in the persistence of the peak mutual information between FSVP and RSVP conditions. We further investigate these differences using a mutual information based functional connectivity analysis and find significant fronto-parietal functional coupling for RSVP and FSVP but no significant coupling for the CSVP condition. We discuss these findings within the context of attentional engagement, evidence accumulation and short-term visual memory.